(untitled) (Research, Society and Development, 2021)
Discussions on chemistry teaching methods have stimulated didactic-pedagogical studies that point out the need to use teaching methods and strategies that provide students with alternatives to overcome learning difficulties. Thus, the main objective of this research was to investigate the effectiveness of using the genre of cordel literature as an active methodology in the teaching and learning of chemistry in high school. The study was characterized for being basic, with a quantitative-qualitative methodological approach, through bibliographic and fieldwork, and in terms of its objectives it is descriptive and exploratory. The research population is composed of Chemistry teachers and students of technical courses integrated to the high school of the Federal Institute of Maranhão - IFMA, Caxias Campus. The percentage of the sample was defined after the quantitative survey conducted to teachers and students. Regarding the elaboration of the data collection instruments, the model suggested by Marconi and Lakatos (2017) was used followed by the respective application of semi-structured questionnaires. As for data processing, the Microsoft Excel program - version 2016 was used for the tabulation and generation of graphs, and subsequent analysis and discussion of the results. At the end of the study, it was found that the textual genre cordel literature contributed significantly to the teaching and learning of chemistry as a tool to promote the production of scientific knowledge.